Danggui Buxue Tang, a Chinese Herbal Decoction Containing Astragali Radix and Angelicae Sinensis Radix, Modulates Mitochondrial Bioenergetics in Cultured Cardiomyoblasts - Kwan, Kenneth K.L.; Huang, Yun; Leung, Ka W.; Dong, Tina T.X.; Tsim, Karl W.K. (Frontiers in Pharmacology, 2019)
Danggui Buxue Tang (DBT) is an ancient herbal mixture containing Astragali Radix and Angelicae Sinensis Radix, and which is a commonly consumed for “Qi-invigorating” as a traditional Chinese medicine (TCM). The pharmacological activities of DBT in anti-oxidation, estrogenic, hematopoietic and immunogenic have been reported; however, the role of DBT in energy metabolism in cellular level has not been determined. Here, we employed an extracellular flux analyzer to evaluate the mitochondrial respiration of cultured cardiomyoblasts in the present of DBT. The herbal extract of DBT was qualified chemically for major ingredients within the decoction, i.e. astragaloside, calycosin, formononetin, Z-ligustilide and ferulic acid. The anti-oxidant activities of DBT, as well as its major ingredients, were determined by Folin-Ciocalteu assay, DPPH radical scavenging assay and protective effect in tert-butyl hydroperoxide (tBHP)-treated cultured cardiomyoblasts, H9C2 cells. In addition, a real-time oxygen consumption rate (OCR) in herbal extract-treated cultured cardiomyoblasts was revealed by using a Seahorse extracellular flux analyzer. In addition, the transcript expressions of PCG-1 and other genes related to mitochondria biogenesis were determined in cardiomyoblasts under different treatments of herbal extracts. DBT possessed the strongest anti-oxidant activity and protective effects to the oxidatively stressed cardiomyoblasts. By revealing the OCR in mitochondria, the health state of cultured cardiomyoblasts under DBT was improved via increase of basal respiration, proton leak, non-mitochondria and ATP production. Furthermore, the transcriptional activities of genes responsible for mitochondrial biogenesis and DNA replication were stimulated by application of DBT in cultures.